Influence of Operational Conditions on the Bottom Corrosion of Atmospheric Storage Tanks and Predicting Model Identification - Maria Francesca Milazzo; Elpida Piperopoulos; Amani Khaskhoussi; Giuseppe Scionti; Paolo Bragatto; Edoardo Proverbio (Chemical Engineering Transactions, 2022)
The assessment of the integrity of atmospheric storage tanks supports in preventing the release of dangerous substances with serious consequences for humans and the environment. In particular, the control of localised thickness losses in the bottom (due to pitting or other phenomena) is essential since these could lead to the perforation of the plates. The aim of this work is to investigate the influence of operational parameters on the corrosion rate of the bottom of storage tanks containing hydrocarbons. The aggressiveness of the solution, the pH and the atmospheric temperature are the investigated parameters in order to evaluate the behaviour over the time of the material used to construct the bottom plates. Carbon steel is considered as reference material. Two different solutions (pH 4 and pH 2.5) are adopted to simulate the presence of impurities in the hydrocarbon. The results represent the starting point to obtain useful information to be used in statistical models for the derivation of the probability of the critical pit. This study has been conducted within the projects “Smart maintenance of industrial plants and civil structures using 4.0 monitoring technologies and prognostic approaches” (MAC4PRO) and “Combined data-driven and experience-driven approach to systemic risk analysis” (DRIVERS), funded by INAIL, and gave a contribution to the knowledge of the evolution of the deterioration mechanism aimed at extending the residual lifetime and the time before the next inspection.